ABOUT THE HISTORY OF THE DISTRIBUTION OF THE AFGHAN PRESS IN THE TERRITORY OF THE BUKHARA EMIRATE (Scientific journal of the Fergana State University, 2024)
In the article the formation of the mass media in Afghanistan, establishment of printing facilities, the first Afghan media outlet “Shams an-nakhar” and its brief description, the aspects praising the emir of Afghanistan Sheralikhan, the impact of the enlightenment movement of Afghanistan to Bukhara, the insolvency of the this media outlet during the Anglo-Afghan war, the launch of “Siraj al-Akhbar Afghania” newspaper, the processes of infiltration of this newspaper to emirate of Bukhara and the Turkistan region, some info on the editing and printing issues in Afghanistan appearing in the local media of Bukhara, architectonics of the newspaper “Siraj al-Akhbar Afghania”, its propagation of independence, the solidarity of Muslims, its propagation of independence, its prohibition in the governorship-general of Turkestan and the emirate of Bukhara, the contemporary location where the newspaper is preserved, the issues related with printing under the name “Amani Afghan” are revealed thoroughly based on the mass media outlets